The Internet Book Circulation Model. - Kotuła, Sebastian Dawid (Information, Medium & Society: Journal of Publishing Studies, 2020)
The history of the development of books can be divided into two stages, the period of manuscripts and the period of prints, each period having slightly different characteristics. The social circulation of manuscripts and early printed books had different structures, showing different paths of circulation. These can be traced back to specific models introduced into the scientific discourse. In the second half of the twentieth century, with the spread of the internet and the digital environment, a new method of book circulation began to take shape: digital and internet-based circulation. The purpose of this article is to present and discuss a model of book circulation via the internet. The model has been based primarily on previous theories originally developed in order to analyze book history, book studies, bibliographical studies, electronic publishing, and literary studies.